A Delphi-based index system for digital transformation capability of retailers - Pan, Jianlin; Lin, Jie; Wang, Siwei (Journal of Business Economics and Management, 2022)
Digital transformation capability (DTC), as an important capability to use digital technology to innovate business and management models, enables retailers reduce costs, and enhance production. It is the main driving force for restructuring the business ecosystem of retailers. To develop the DTC of retailers, an index system is required to provide capability standards. Hence, the construction of an index system for retailers’ DTC is of important research value. However, there are few studies on the DTC of retailers, and no representative capability model or index system has been formed. Therefore, based on the definition of related concepts of DTC and literature review, this paper puts forward the research proposition of “index system for retailers’ DTC”, aiming to build an operable and applicable index system. According to the research process of the Delphi method, the present paper constructs an index system for retailers’ DTC through two rounds of expert consultations. The proposed system consists of three primary indices (e.g., technological change capability), 11 secondary indices (e.g., digital infrastructure) and 41 tertiary indices (e.g., datacenter), offering a capability development standard for the digital transformation of retailers. The research results also provide a reference for the digital transformation of retailers in the real world.First published online 15 September 2022